EDUCAÇÃO INFANTIL NA ESCOLA DO CAMPO: UMA ABORDAGEM A PARTIR DAS ILHAS INTERDISCIPLINARES NA PERSPECTIVA DA EDUCAÇÃO INTEGRAL - Almeida, Lia Heberlê de; Camargo, Thiago Dutra de; Miletto, Milene Ferreira (Revista de Ciências Humanas, 2025)
The present study presents an Interdisciplinary Island of Rationality (IIR) developed in the post-pandemic period, during the return of face-to-face classes, in an Early Childhood Education (ECE) class of a Rural School. It aims to theoretically analyze the development of an IIR in ECE in the Countryside from the approximation of references of the IIR (Fourez, 1997; 2005), Integral Education (Moll et al., 2012) and Rural Education (Caldart, 2011; 2012). It is characterized as an Experience Report developed in the municipal school network of São Gabriel in a school in the rural area. The activities involved a teacher, the school principal and twelve Early Childhood Education students aged 4 and 5 years. The results indicate that the context of the pandemic has further accentuated social and educational inequality with regard to rural peoples. However, the IIR analyzed demonstrated its potential in the construction and articulation of knowledge, especially for a human and integral education, pointing out as a didactic strategy for the construction of meaningful learning.